Decolonizing the Mind: Schwimmer, Habermas and the Anthropology of Postcolonialism - Clammer, John (Anthropologica, 2022)
Running through the anthropological work of Eric Schwimmer is a constant encounter with postcolonialism. Unlike the more conventional forms of postcolonial theory, Schwimmer draws on a vocabulary derived from symbolic anthropology, semiotics, the anthropology of religion and most recently ecology. In doing so he has provided a theory of the role of ontologies in framing the negotiated sociocultural predicaments of postcolonial societies rooted in his ethnographic work in Melanesia and Polynesia and with indigenous peoples and settlers in Quebec. This essay explores this dimension of Schwimmer's work and develops a comparison between his approach to the decolonization of the mind and that of Jurgen Habermas. In doing so it attempts to show both the innovative and nuanced nature of Schwimmer's postcolonial anthropology and its utility in addressing the issues of globalization, the successor to colonialism as the current world transformative movement.